Berbicara Dengan Logika: Strategi Komunikasi Yang Efektif Dalam Proses Pembelajaran - Yurniman Ndruru; Yurlina Ndruru; Mozes Lawalata (Lembaga Pengembangan Kinerja Dosen, 2024)
: Speaking with logic is an effective communication strategy in the learning process that can enhance students' understanding and retention of information. This article discusses the importance of using logic in communication within the classroom to facilitate effective learning. Firstly, the article outlines the concept of speaking with logic and explains how this approach can strengthen understanding of course material. Furthermore, the article highlights several practical strategies that educators can employ to apply logic in speaking within the classroom, including using consistent arguments, strong premises, and avoiding logical fallacies. Additionally, the article emphasizes the importance of fostering a classroom environment conducive to logical and open discussions. Through the implementation of these strategies, it is hoped that the learning process can become more structured, meaningful, and effective for students.